2017
DOI: 10.1186/s12967-017-1184-x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results demonstrating the impact of Mediterranean diet on bone health

Abstract: BackgroundNutrition is an environmental factor affecting bone health. Nutrition is considered essential to achieve and maintain optimal bone mass. Mediterranean diet (MD) has shown to prevent bone disease. Aim of this study is to investigate the relationship between bone health status and adherence the MD.MethodsFour-hundred eighteen healthy people (105 males and 313 females, age 50 ± 14 years) were recruited in the outdoor hospital of the “Campus Salute Onlus” held in Piazza del Plebiscito in Naples, October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…We have recently reported that the dietary intake of long-chain omega-3 polyunsaturated fatty acid is positively associated with BMD at both the hip and the lumbar spine [ 15 ] as well as fish consumption [ 20 ]. Taken together, those results are consistent with studies that reflect that a dietary pattern compatible with the Mediterranean diet has positive effects over bone health parameters [ 7 , 8 , 21 ]. Thus, those results are consistent with the hypothesis that dietary factors may contribute to better bone health.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have recently reported that the dietary intake of long-chain omega-3 polyunsaturated fatty acid is positively associated with BMD at both the hip and the lumbar spine [ 15 ] as well as fish consumption [ 20 ]. Taken together, those results are consistent with studies that reflect that a dietary pattern compatible with the Mediterranean diet has positive effects over bone health parameters [ 7 , 8 , 21 ]. Thus, those results are consistent with the hypothesis that dietary factors may contribute to better bone health.…”
Section: Discussionsupporting
confidence: 92%
“…In another clinical follow-up of patients who regularly consumed olive oil over a 1-year period, bone mineral density (BMD) at lumbar vertebrae L3, L4, and the femoral neck had also improved [ 6 ]. The relation of bone health and olive oil consumption has also been evaluated by means of calcaneal quantitative ultrasound (QUS), showing that higher T-scores were positively associated with a higher consumption of extra-virgin olive oil [ 7 ]. A high consumption of fish and olive oil and low red meat intake has also been positively related to bone mass in adult women, suggesting the potential bone-preserving properties of this dietary pattern throughout adult life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The BIA phase-sensitive system (800 µA, 50 kHz; BIA 101 RJL, Akern Bioresearch, Florence, Italy) was used by experienced observers to assess body composition [19] as previously reported [17,[20][21][22]. We performed the exam as suggested by the European Society of Parental and Enteral Nutrition (ESPEN) [23].…”
Section: Bioelectrical Impedance Analysismentioning
confidence: 99%
“…; Savanelli et al . ). These positive outcomes from a Mediterranean diet support wider investment in nutritional strategies and dietary change to improve health in older adults.…”
Section: Personalising Nutrition For Older Adultsmentioning
confidence: 97%